Evidence for anti-inflammatory activity of isoliquiritigenin, 18β glycyrrhetinic acid, ursolic acid, and the traditional Chinese medicine plants Glycyrrhiza glabra and Eriobotrya japonica, at the molecular level - Zhou, Junxian; Wink, Michael (Medicines, 2019)
Background: We investigated the effect of root extracts from the traditional Chinese medicine (TCM) plants Glycyrrhiza glabra L., Paeonia lactiflora Pall., and the leaf extract of Eriobotrya japonica (Thunb.) Lindl., and their six major secondary metabolites, glycyrrhizic acid, 18β glycyrrhetinic acid, liquiritigenin, isoliquiritigenin, paeoniflorin, and ursolic acid, on lipopolysaccharide (LPS)-induced NF-kB expression and NF-kB-regulated pro-inflammatory factors in murine macrophage RAW 264.7 cells. Methods: The cytotoxicity of the substances was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) method. RAW 264.7 cells were treated with LPS (1 μg/mL) or LPS plus single substances; the gene expression levels of NF-kB subunits (RelA, RelB, c-Rel, NF-kB1, and NF-kB2), and of ICAM-1, TNF-α, iNOS, and COX-2 were measured employing real-time PCR; nitric oxide (NO) production by the cells was quantified with the Griess assay; nuclear translocation of NF-kB was visualized by immunofluorescence microscopy with NF-kB (p65) staining. Results: All the substances showed moderate cytotoxicity against RAW 264.7 cells except paeoniflorin with an IC50 above 1000 μM. Glycyrrhiza glabra extract and Eriobotrya japonica extract, as well as 18β glycyrrhetinic acid and isoliquiritigenin at low concentrations, inhibited NO production in a dose-dependent manner. LPS upregulated gene expressions of NF-kB subunits and of ICAM-1, TNF-α, iNOS, and COX-2 within 8 h, which could be decreased by 18β glycyrrhetinic acid, isoliquiritigenin and ursolic acid similarly to the anti-inflammatory drug dexamethasone. NF-kB translocation from cytoplasm to nucleus was observed after LPS stimulation for 2 h and was attenuated by extracts of Glycyrrhiza glabra and Eriobotrya japonica, as well as by 18β glycyrrhetinic acid, isoliquiritigenin, and ursolic acid. Conclusions: 18β glycyrrhetinic acid, isoliquiritigenin, and ursolic acid inhibited the gene expressions of ICAM-1, TNF-α, COX-2, and iNOS, partly through inhibiting NF-kB expression and attenuating NF-kB nuclear translocation. These substances showed anti-inflammatory activity. Further studies are needed to elucidate the exact mechanisms and to assess their usefulness in therapy.
Gesehen am 23.10.2019